2019
DOI: 10.1051/0004-6361/201936824
|View full text |Cite
|
Sign up to set email alerts
|

Searching for further evidence for cloud–cloud collisions in L1188

Abstract: In order to search for further observational evidence of cloud-cloud collisions in one of the promising candidates, L1188, we carried out observations of multiple molecular lines toward the intersection region of the two nearly orthogonal filamentary molecular clouds in L1188. Based on these observations, we find two parallel filamentary structures, both of which have at least two velocity components being connected with broad bridging features. We also found a spatially complementary distribution between the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 80 publications
0
1
0
Order By: Relevance
“…Recent observational studies provide ample evidence supporting the key role played by CCC in star formation. Studies have shown induced high-mass star and cluster formation (e.g., Issac et al 2020a;Fukui et al 2021), formation of super star clusters (e.g., Fukui et al 2014Fukui et al , 2016, low-and intermediate-mass stars (e.g., Gong et al 2017Gong et al , 2019 and massive star clusters (e.g., Sano et al 2018;Issac et al 2020a). CCC resulting in the formation of single O-type stars with surrounding H II regions has also been observed (e.g., Torii et al 2015Torii et al , 2017.…”
Section: Introductionmentioning
confidence: 99%
“…Recent observational studies provide ample evidence supporting the key role played by CCC in star formation. Studies have shown induced high-mass star and cluster formation (e.g., Issac et al 2020a;Fukui et al 2021), formation of super star clusters (e.g., Fukui et al 2014Fukui et al , 2016, low-and intermediate-mass stars (e.g., Gong et al 2017Gong et al , 2019 and massive star clusters (e.g., Sano et al 2018;Issac et al 2020a). CCC resulting in the formation of single O-type stars with surrounding H II regions has also been observed (e.g., Torii et al 2015Torii et al , 2017.…”
Section: Introductionmentioning
confidence: 99%